2018
DOI: 10.1021/acs.jafc.8b05879
|View full text |Cite
|
Sign up to set email alerts
|

New Rice-Derived Short Peptide Potently Alleviated Hyperuricemia Induced by Potassium Oxonate in Rats

Abstract: Gout that caused by hyperuricemia affects human health seriously and more efficient drugs are urgently required clinically. In this study, a novel peptide named RDP1 (AAAAGAKAR, 785.91 Da) was identified from the extract of shelled fruits of Oryza sativa. Our results demonstrated that RDP1 (the minimum effective concentration is 10 μg/kg) could significantly reduce the serum uric acid and creatinine and alleviate hyperuricemic nephropathy in rats by intragastric administration. RDP1 inhibited xanthine oxidase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…The gut microbiota is established during the development of the host, and its composition and metabolism are closely associated with chronic metabolic syndromes. 29,30 Although various studies have shown that antihyperuricemia effects of protein hydrolysates in cell and mice models, 7,31 the underlying mechanism and the modulation effects of the protein hydrolysates on gut microbiota, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gut microbiota is established during the development of the host, and its composition and metabolism are closely associated with chronic metabolic syndromes. 29,30 Although various studies have shown that antihyperuricemia effects of protein hydrolysates in cell and mice models, 7,31 the underlying mechanism and the modulation effects of the protein hydrolysates on gut microbiota, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule phytochemicals (flavonoids, anthocyanins, alkaloids, etc) have been the focus of treatments for hyperuricemia and renal inflammation for many years, and commonly their therapeutic target is only one of the pathways involved in uric acid metabolism or inflammatory signaling regulation. 3,7,8 However, due to the difficulty in producing and storing small molecule compounds, biomacromolecules with high activity, stability, and specificity, such as active oligopeptides, have attracted increasing interest in alleviating hyperuricemia. Various novel peptides were isolated, and their dose-dependent antihyperuricemia effects and mechanisms were investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…and UA excretion promoters (probenecid, benzbromarone, etc.) [26]. Although these drugs aid in reducing UA levels, many exhibit serious side effects, such as gastrointestinal reactions, skin rashes, liver and kidney dysfunction, and hepatotoxicity [27].…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that this peptide inhibited XO in vitro and in vivo, probably by occupying the binding site to xanthine (docking studies). Furthermore, no acute toxicity in rats was observed, and authors also evidenced that RDP-1 was stable in several temperatures [105].…”
mentioning
confidence: 98%